The Measurement Problem in Values-Based Curriculum Management: A Systematic Review of Affective Assessment Instruments in Islamic Educational Institutions - Parino; Agus Subagya; Mahmudi (EDUJAVARE: International Journal of Educational Research, 2026)
The Indonesian Ministry of Religious Affairs introduced the Love-Based Curriculum (Kurikulum Berbasis Cinta, KBC) through Ministerial Decree No. 1503 of 2025, requiring every madrasah to organise intracurricular, cocurricular, and extracurricular activity around five affective commitments known as Panca Cinta. Scholarship has described how madrasah leaders plan and enact this curriculum, yet the evaluative function of curriculum management has attracted far less attention. This review examines how affective outcomes are assessed within values-based curriculum management in Islamic educational institutions, which instruments are reported, what psychometric evidence supports them, and what obstacles prevent measurement. Following the PRISMA 2020 statement, the review searched Scopus, ERIC, DOAJ, Garuda, and Google Scholar for studies published between 2015 and 2026, screened 316 unique records, and retained 30 studies for synthesis. Screening agreement between two independent reviewers was substantial. Thematic synthesis produced four findings. First, affective targets are stated at the level of dispositions rather than behaviours, which leaves them unobservable. Second, assessment practice depends almost entirely on teacher observation, anecdotal records, and documentary evidence collected at classroom level; institutional and supervisory indicators are absent from the corpus. Third, no included study reported construct validity evidence or a reliability coefficient for an affective instrument. Fourth, the barriers reported by practitioners are managerial rather than pedagogical, concerning indicator specification, reporting alignment, and supervisory capacity. The review proposes a three-tier assessment architecture linking classroom evidence, institutional indicators, and supervisory verification, and translates Panca Cinta into low-inference observable indicators. Measurement is positioned as a control function of curriculum management rather than a technical accessory to instruction